Shear wave elastography to evaluate the effect of serum uric acid levels on carotid artery elasticity in patients with high-normal blood pressure: Effects of SUA on carotid artery elasticity in patients with high-normal BP - Wang, Yifan; Wang, Xinyu; Li, Xiya; Li, Zhen; Zhang, Mengmeng; Zhang, Siran; Ma, Le; Huang, Dongmei; Li, Guangsen (Journal of Medical Biochemistry, 2024)
Background: Populations with normal high blood pressure often already have elevated blood uric acid levels and a higher chance of developing atherosclerosis, which accelerates the process of cardiovascular disease. The risk of atherosclerosis increases with thickening of the carotid artery intima-media, and changes in carotid artery elasticity precede intima-media changes, so early monitoring of carotid artery elasticity is of great significance in the prevention of cardiovascular disease. Using shear wave elastography (SWE) to evaluate the effect of serum uric acid (SUA) levels on carotid artery elasticity in patients with high-normal blood pressure (BP).Methods: One hundred and fifteen patients with high-normal BP were selected, and then divided into tertiles according to the SUA levels. The left carotid intima-media thickness (IMT), peak systolic velocity (PSV) and diameter of common carotid artery were measured by two-dimensional ultrasound and Doppler flow imaging. Longitudinal elasticity of the left anterior carotid wall was measured by SWE, including the mean values of the minimum elastic modulus (MEmin), maximum elastic modulus (MEmax) and mean elastic modulus (MEmean). Results: IMT, MEmean, MEmin and MEmax were obviously higher in the 3rd tertile (all P < 0.05), while there were no obviously different between the 1st tertile and 2nd tertile. Pearson correlation analysis showed positive correlations between SUA and SWE-related parameters, while there was no correlation with IMT. Multiple linear regression analysis found that age, systolic BP, and SUA levels were independently associated with SWE-related parameters. Conclusion: SWE will be more helpful than IMT in monitoring the effect of blood uric acid levels on carotid artery elasticity in patients with high-normal BP.